The study of gene polymorphisms in neurotransmitter systems (HTR1A and SLC6A3) and morphofunctional characteristics in students with depression symptoms = Badanie genowego polimorfizmu systemów neurotransmiterów (HTR1A oraz SLC6A3) oraz charakterystyka morfofunkcjonalna u studentów zobjawami depresji - Negasheva, Marina; Vasileva, Aleksandra; Godina, Elena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the last decades, due to the increasing level of stress, the study of different de-pressive states and search for morpho-functional and genetic markers of depression have become important for modern society. This article is an interdisciplinary study of morpho-functional characteristics and variability of genes in the neurotransmitter systems (HTR1A and SLC6A3) in young men and women with the expression of depressive symptoms.
Keywords: charakterystyka morfofunkcjonalna; symptomy depresji; geny; systemy neurotransmiterów; morpho-functional characteristics; depression symptoms; genes of neurotransmitter systems